THE INFLUENCE OF DELEGATIVE LEADERSHIP AND TEACHER PERFORMANCE ON STUDENT ACHIEVEMENT THROUGH THE MERDEKA BELAJAR POLICY IN JEMBER ELEMENTARY SCHOOLS - Sebifera, Mella Rosa; Nursaid, Nursaid; Sanosra, Abadi (LPPM STIE Muhammadiah Bandung, 2025)
This study investigates the influence of delegative leadership and teacher performance on student achievement in the context of Jember Regency's elementary schools, with the Merdeka Belajar (Freedom to Learn) policy as a mediating variable. Utilizing a quantitative approach, data were collected from 289 schools using questionnaires and analyzed through Partial Least Squares (PLS) with WarpPLS software. The findings reveal significant direct effects of delegative leadership and teacher performance on both the implementation of the Merdeka Belajar policy and student achievement. Furthermore, the Merdeka Belajar policy mediates the relationships between delegative leadership, teacher performance, and student achievement. This research integrates the Expectancy-Value Theory and Multi-Level Perspective framework, providing a novel understanding of the dynamics between leadership, teacher performance, policy implementation, and educational outcomes. The results emphasize the critical role of leadership empowerment, teacher development, and effective policy implementation in improving educational quality and student outcomes. These insights offer valuable implications for future educational strategies and policy development in Indonesia.